Designed fields: increasing the collaboration between landscape architecture and sustainable agriculture in the design of multifunctional landscapes - Mader, Grace (Kansas State University, 2020)
Traditionally, sustainable agriculture has been focused on soil health and the economics of production, however, this definition is now broadening to include ecology and education. The goal of sustainable agricultural practices is to minimize the adverse effects of farming on surrounding ecosystems and instead strive for long-term stability of the entire agricultural enterprise, environmental protection, and consumer safety (McDonnell 2011; Powlson et. al. 2011). Landscape architecture is the design of outdoor space to achieve environmental, social, and/or aesthetic outcomes (Jellicoe, 1975). Though landscape architecture has traditionally leaned towards aesthetics and social interaction, since the mid-20th century the work of many landscape architects has shifted towards ecological sensitivity while maintaining existing aesthetic and sociological functions. Today, sustainable agriculture and landscape architecture are becoming even more similar and face many of the same challenges. Although key differences remain, both fields emphasize ecology, economics, sociology, and aesthetics (Hill, 2016; Yu, 2016). Despite overlaps in design considerations and outcomes of intervention, the two fields and those working within them, rarely collaborate. In this project, landscape architecture and sustainable agriculture theories, principles, and research are studied in order to clearly illustrate their similarities and differences. The fields are compared to identify areas where existing knowledge bases overlap. Examples of successful and unsuccessful collaboration between the fields to design and implement multifunctional landscapes in urban and peri-urban environments are researched and analyzed according to a series of metrics to determine successes, failures, and opportunities for improvement. The analysis of existing projects in combination with a rich understanding of the fields result in a series of projective design strategies and culminate in a single design project. The final design project, Twin Lakes Park in Homer Glen, IL, is a 250-acre property consisting primarily used for corn and soybean farming. The property is redesigned into a multi-functional agricultural landscape and park. The new design of Twin Lakes Park is analyzed according to the same metrics as the selected case studies in order to identify successes and failures within the design and within the metrics themselves. Final metrics and design strategies have the potential to influence existing landscape performance metrics and sustainable site strategies, encouraging a greater degree of collaboration between the fields of landscape architecture and sustainable agriculture.
Keywords: sustainable agriculture; landscape architecture; rural landscapes; multifunctional landscapes; Chicago